Optimalisasi Kompetensi Profesional Guru Sekolah Menengah Pertama Melalui Kegiatan Pengembangan Asesmen Formatif Literasi Sains - Mentari Darma Putri; Ahmad Fauzi Syahputra Yani; Dini Fitria (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The scientific literacy formative assessment is an instrument designed with the aim of improving students' scientific literacy skills. Based on interviews conducted with the Principal of SMP Negeri 4 Langsa, it is known that the teachers' skills in compiling scientific literacy formative assessment instruments are still low. This is because training regarding formative assessment of scientific literacy has not been evenly distributed among teachers at SMP Negeri 4 Langsa. Therefore, it is necessary to hold training in preparing formative assessments of scientific literacy for teachers at SMP Negeri 4 Langsa. Methods for implementing activities include: 1) planning, 2) implementation, 3) monitoring and evaluation. This community service activity aims to increase the knowledge, understanding and skills of junior high school teachers in Langsa City in developing learning assessments in the form of scientific literacy formative assessments. The results of the PKM activities showed that the pre-test and post-test scores for teachers' scientific literacy formative assessment knowledge increased from an average of 72 to an average of 84. The satisfaction questionnaire also showed that teachers were satisfied with the PKM activities. Apart from that, it was also concluded from the questionnaire that teachers' knowledge and skills related to formative assessment of scientific literacy increased.